The use of eculizumab as a bridge to retransplantation for chronic antibody-mediated rejection in a heart transplant recipient: a case report. Issue 5 (11th May 2021) - Kearney, Katherine; Macdonald, Peter; Hayward, Christopher; Muthiah, Kavitha
Abstract: Background: Antibody-mediated rejection (AMR) remains a major management challenge in heart transplantation given the complexity of pathological diagnosis and dearth of evidence for effective management. Eculizumab, an anti-C5 monoclonal antibody which inhibits terminal complement activation, has been reported to decrease early AMR in sensitized renal transplant recipients. Case summary: We report a case of a 29-year-old gentleman with chronic AMR 8 years after heart transplantation, manifesting as significant graft dysfunction. Donor-specific antibodies to DQ7 were found to be causative. Antibody-mediated rejection was managed with quadruple oral immunosuppressive therapy (mycophenolate, prednisolone, everolimus, and tacrolimus) as well as a sequence of broad-spectrum immunological therapies; intravenous (IV) methylprednisolone, plasmapheresis, IV immunoglobulin, rituximab, bortezomib, tocilizumab, and splenic irradiation. No treatment had a sustained impact on donor-specific anti-HLA antibodies (DSAs) or graft function. After testing showed the DQ7 antibodies were complement-binding, a trial of eculizumab was started. This improved DSAs somewhat, and improved graft function and New York Heart Association functional class substantially. The patient was relisted for heart transplantation and successfully retransplanted in March 2018. Specifically, the new organ and recipient were matched at DQ7. After discontinuation of eculizumab, the patient has remained healthy and well, with normal graft function 28 months after retransplantation. Discussion: To the best of our knowledge, this is the first case of chronic AMR in a heart transplant patient, successfully stabilized with eculizumab and bridged to retransplantation.